Glutathione S-transferase T1- and M1-null genotypes and coronary artery disease risk in patients with Type 2 diabetes mellitus Cardiovasc. (January 2009) - Manfredi, Samantha; Calvi, Debora; del Fiandra, Martina; Botto, Nicoletta; Biagini, Andrea; Andreassi, Maria Grazia
Introduction: Since long-term exposure to oxidative stress is strongly implicated in the pathogenesis of diabetic complications, polymorphic genes of detoxifying enzymes must be involved in the development of coronary artery disease (CAD). We assessed the potential glutathione S-transferase (GST) gene––gene (GSTM1 null ––GSTT1 null ) and gene––smoking interactions on the development of CAD in patients with Type 2 diabetes.Materials & methods: In a case-only design, we enrolled 231 patients with Type 2 diabetes (147 male, 66.1 ±± 9.7 years) referred to our institute for coronary angiography investigation. CAD was diagnosed if there was over 50% obstruction of one or more major vessels.Results: Coronary angiography revealed significant CAD in 184 patients (80%). Male gender (p < 0.001), smoking habits (p = 0.003) and GSTT1 null genotype (p = 0.003) were significantly correlated with the increasing extent of the coronary atherosclerosis. Case-only analysis revealed that patients with both M null ––T null genotypes had the highest risk for 3-vessel CAD compared with patients who express both GST genes (odds ratio: 3.1; 95% confidence interval: 1.0––10.3, p = 0.04). A nearly threefold interaction existed between cigarette smoking and M null ––T null genotypes (odds ratio: 2.9, 95% confidence interval: 1.7––7.8, p = 0.03). A significant interaction between M null ––T null genotypes and smoking was also observed on the increasing number of coronary vessels that were diseased (χχ 2 = 14.0; p = 0.03).Conclusion: These data suggest that polymorphisms in GSTM1 and GSTT1 genes are risk factors for CAD in Type 2 diabetic patients, especially among smokers. These genetic markers may permit the targeting of preventive and early intervention on high-risk patients to reduce their cardiovascular risk.